Preliminary Investigation Of Automobile Hydraulic Transmission System - Ahmad Zaki , Abd Razak (UTeM, 2008)
This study is to investigate an alternative approach for full hydraulic transmission system in automotive application. A transmission system, which consists of hydraulic components, is to be analyzed by replacing the common mechanical type transmission system of a vehicle to observe its potential on whether the transmission system which is fully driven by the hydraulic components can cater the currently available mechanical transmission system. It is also an alternative approach to reduce the fuel consumption. By reducing the driving capacity, a preliminary investigation was conducted to obtain the information regarding full hydraulic transmission system before any enhancement can be carried out to improve the system. Next, critical selection and calculation were done in order for the hydraulic transmission to be working efficiently by identifying parameters involved in this research. The result is based on the selection of parameters values which appropriate to the system.